2020
DOI: 10.1002/nau.24442
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in the persistence of stress urinary incontinence from postpartum to 12 years after first delivery

Abstract: Aims The aim of this study was to investigate constitutional‐, pregnancy‐, labor‐, and delivery‐related factors involved in the long‐term persistence of stress urinary incontinence (SUI) from 6 months postpartum to 12 years after first delivery. We also evaluated severity and impact on quality of life of persistent SUI. Methods This was a longitudinal study including primigravid women who gave birth at our Public Health Hospital during 2007. Urinary symptoms were investigated at inclusion, 6 months and 12 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
(33 reference statements)
0
9
0
2
Order By: Relevance
“…The total score ranges from 0 (no UI) to 21 (very severe problem). The total score is divided into four categories: slight (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and very severe (19)(20)(21) [12]. A fourth question on the occurrence of symptoms of UI was used to indicate SUI, UUI and MUI [13].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total score ranges from 0 (no UI) to 21 (very severe problem). The total score is divided into four categories: slight (1-5), moderate (6)(7)(8)(9)(10)(11)(12), severe (13)(14)(15)(16)(17)(18), and very severe (19)(20)(21) [12]. A fourth question on the occurrence of symptoms of UI was used to indicate SUI, UUI and MUI [13].…”
Section: Methodsmentioning
confidence: 99%
“…However, up to 91% of women with SUI after their first delivery still report SUI 12 years later [21]. Although UI is not life threatening, women in the general population with UI report lower health-related quality of life and mental wellbeing and 45% of women report a moderately to totally (19)(20)(21) 0 (0) 0 (0) 0 (0) 0 (0) N = number, % = percentage, SD = standard deviation, CI = confidence interval, UI = urinary incontinence, SUI = stress urinary incontinence, UUI = urgency urinary incontinence, MUI = mixed urinary incontinence, ICIQ-UI-SF = International Consultation on Incontinence Questionnaire Urinary Incontinence Short Form limiting effect on exercise [22]. Women with UI in this study reported significant bother of UI regarding physical activities like in the study of Monz et al [22].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Prolonged second stage of labor among 4 studies with over 5800 participants had a nonsignificant increased odds of UI (OR, 1.19; 95% CI, 0.94‐1.52). However, by 12 years after birth in the above‐mentioned cohort study, active pushing longer than one hour was associated an OR of 3.68 (95% CI, 1.21‐11.14), although this was not identified as a factor at 12 months postpartum 7,8 . In a separate meta‐analysis of 7 studies, Smeets et al calculated no association between avulsion of the pubic portion of the levator ani during birth and UI (adjusted OR [aOR], 0.72; 95% CI, 0.40‐1.30) among 22 studies with nearly 11,500 particpants 9 …”
Section: Paying Attention To the Pelvic Floor In Pregnancy And Postpartummentioning
confidence: 96%
“…UI persists during the postpartum for about 30% of people, decreasing with time to 11% reporting symptoms by one year after birth 7 . A cohort study following over 300 people with UI at 6 months postpartum found 80% still had symptoms at 12 years 8 . The largest risk factor for UI postpartum identified in the meta‐analysis by Hage‐Fransen et al was its presence during pregnancy.…”
Section: Paying Attention To the Pelvic Floor In Pregnancy And Postpartummentioning
confidence: 99%
See 1 more Smart Citation